Use of avocado peel (Persea americana) in tea formulation: a functional product containing phenolic compounds with antioxidant activity - Rotta, Eliza Mariane; Morais, Damila Rodrigues de; Biondo, Polyana Batoqui França; Santos, Vanessa Jorge dos; Matsushita, Makoto; Visentainer, Jesui Vergilio (Acta Scientiarum. Technology, 2015)
The peels of avocados, like other fruit peels, are commonly discarded, not knowing their potential use. In order to reuse avocado peel, the chemical and mineral compositions, total phenolic and flavonoid contents as well as antioxidant activities have been investigated by DPPH (1,1-diphenyl-2-picrylhydrazyl) and FRAP(ferric-reducing antioxidant power) methods in in natura and dehydrated avocado peel. Dehydrated avocado-peel tea was manufactured and the antioxidant activity was evaluated, as well as their flavonoid and phenolic compound contents, and compared with other teas marketed. Avocado peel, especially dried avocado peel, contains major phenolic compounds (10,848.27 Â± 162.34 mg GAE kg-1) and flavonoids (1,360.34 Â± 188.65 mg EQ kg-1). The avocado-peel tea showed antioxidant activity by DPPH (1,954.24 Â± 87.92 e 2518.27 Â± 192.59 mg TE L-1) and phenolic and flavonoids contents highest than apple tea. The avocado-peel tea showed good antioxidant activity and had good acceptability by sensory analysis as a promising product. Â